Intertemporalny wymiar obowiązywania decyzji administracyjnych na przykładzie decyzji ustanawiającej tzw. publiczną służebność przesyłu w kontekście problematyki zasiedzenia służebności gruntowej o treści odpowiadającej służebności przesyłu - Brudziński, Michał (Kwartalnik Prawa Publicznego, 2015)
The main object of this study is an attempt to reconstruct the limits of entitlements which set the essence of the institution known as public transmission easement and the administrative law effects of modifications of these limits due to normative changes in the range of the legal basis of their defining, with the proviso of permanence in the exercise of these entitlements and taking into account the indirect way of binding of norms making up this legal basis that implies the necessity of authoritative concretization of these norms by administrative decision to trigger legal consequences provided for therein. Delimitation of the abovementioned limits and their contextualisation within the framework of issue of doctrinally worked out construct of appurtenant easement which corresponds to transmission easement, a construct which, apart from its dogmatic correctness, in assuming of its theoreticians is intended as a kind of juridical substitute of, sanctioned in 2008 under Polish civil law, institution of transmission easement, so all this will be a justified, according to the author, basis of inference about the possibility and scope of usucaption of appurtenant easement which corresponds to transmission easement in all those, distinguished qualitatively, cases in which an entity authorised under the administrative decision to establish the so-called public transmission easement for its benefit, exercises all entitlements in a manner commensurate with changing generally applicable law, but notwithstanding, going beyond the catalogue of initially granted to him, by that decision, legal capabilities. Scheme of description of above marked out issue area is as follows. In the first part of this paper the author will try to expose the nub of the problem of intertemporality of law provisions in genere and intertemporal validity of the aggravated administrative acts in the case of legislative changes within their legal basis. Then, making use of analysis of provisions of the expropriation law, the author will propose three possible means for resolving the specific issue of the lack of binding statement of the legislator as to the legal existence of administrative acts issued on the basis of provisions derogated from the legal system, i.e. primo their repealing, secundo unconditional petrification of their binding force and tertio making their adequate in terms of content, to finally highlight this one among them, which may be described as praxeologically justified. Lastly, in the latter portion of considerations, the author will make a complementary juxtaposition all of above inferred ascertainments with, falling within the civil law and having been in recent years the subject of numerous controversies, issue of usucaption of an appurtenant easement which corresponds to transmission easement, so that the solution to this complex problem, at least in the analyzed under this study section, is, in his view, closer.